Podatki a struktura własności - Kałdoński, Michał; Mizerka, Jacek (Taxes and Ownership Structure, 2007)
The paper concerns the problem of choosing an organizational and legal form for the firm. The structure of ownership is reflected in the organizational and legal form of running the firm. The authors focus on two extreme forms: sole proprietorship and Corporation. The proposed model of choosing an organizational form is a development of the concept of MacKie-Mason and Gordon. The authors confront an excess of benefits from risk diversification over agency costs with differences in taxation. For the purpose of choosing an organizational form, the authors use the model of valuing an option to switch proposed by Kulatilaka and Trigeorgis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 267-277